“All the world's a stage”: Creating Guanajuato, Mexico’s Tourism Image - Claudia Asch (Études Caribéennes)
This paper will analyze the tourism image the municipal and state tourism offices of Guanajuato, Mexico, a World Heritage site, aim to project through their promotional materials: a small, colonial city, whose streets are shown as empty, cobble-stoned, and set in romantic light. The "city of Cervantes in the Americas" (a title bestowed by UNESCO in 2005 to honor the theatrical tradition of Cervantes plays in Guanajuato) appears to want to set forth an image of tranquility and spaciousness, while the reality is much different: Guanajuato's mainly narrow and windy streets typically bustle, plazas and gardens are full of activity, in short, the town is alive, yet its projected image lacks liveliness. Furthermore, although it is a World Heritage site, Guanajuato has thus far not used that brand to its advantage; instead, Guanajuato has recently had a variety of slogans to promote itself, seemingly at the whim of officials. Through interviews with tourism officials and a selection of collected tourism materials, I show how the city has yet to establish a “coherent” brand, and is going through various phases of place marketing at once.